Il respiro nascosto delle cose. - Meneghelli, Luigi (Verona : Studio La Città, 2001)
Calzolari, Pierpaolo ; Carroll, Lawrence ; Liv, Lena ; Marchelli, Mirco ; Merz, Mario ; Pascali, Pino ; Penone, Giuseppe ; Pistoletto, Michelangelo ; Poli, Mariella ; Silva, Roberta ; Valentini, Nanni ; Wentworth, Richard
biog. p. 32
Il respiro nascosto delle cose, Studio La Città, Verona, 1 Dicembre 2001. Mostre n. 216
Italiaans & Engels
kunstcatalogus